# $\frac1a+\frac1b+\frac1c=0 \implies a^2+b^2+c^2=(a+b+c)^2$? [closed]

How to prove that $a^2+b^2+c^2=(a+b+c)^2$ given that $\frac1a+\frac1b+\frac1c=0$?

-

## closed as off-topic by Davide Giraudo, dfeuer, user1337, Adriano, azimutAug 28 '13 at 22:00

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "Homework questions must seek to understand the concepts being taught, not just demand a solution. For help writing a good homework question, see: How to ask a homework question?." – Davide Giraudo, dfeuer, user1337, Adriano, azimut
If this question can be reworded to fit the rules in the help center, please edit the question.

It will be better if you show at least some of your work or whatever you have attempted ... that way people would be more likely to answer your questions – user67258 Aug 3 '13 at 2:41

Expand the right side:

$$(a+b+c)^2 = a^2 + b^2 + c^2 + 2ab + 2ac + 2bc.$$

From the supplementary condition we have

$$\frac{1}{a}+\frac{1}{b} + \frac{1}{c} = 0$$

Or

$$\frac{ab+ac+bc}{abc} = 0.$$

Therefore $ab+ac+bc = 0$ and the result follows. (None of $a,b,c$ can be $0$ else their inverses would be undefined and so the supplementary condition would be ill-posed.)

-

$(a+b+c)^{2}=a^{2}+b^{2}+c^{2}+2ab+2ac+2bc=a^{2}+b^{2}+c^{2}+2abc\big(\frac{1}{c}+\frac{1}{b}+\frac{1}{a}\big)=a^{2}+b^{2}+c^{2}$

since $\frac{1}{a}+\frac{1}{b}+\frac{1}{c}=0$.

-